Implementasi Kurikulum 2013 Pada SMK di Kabupaten Lombok Timur - Kholisho, Yosi Nur; Marfuatun, Marfuatun (Jurnal Pendidikan Informatika (EDUMATIC), 2018)
Vocational School is an education that prepares students to be ready to work held at the secondary school level. The purpose of this study (1) to find out how the curriculum 2013  implementation in schools; (2) what are the obstacles in implementing the curriculum 2013. The type of research used is descriptive research. This study used 12 vocational schools in 8 sub-districts. The results of the curriculum  2013 implementation data in schools showed that 94.44% of the majority of  curriculum 2013implementations had been implemented, 2.78% were fully implemented and 2, 78% were mostly implemented. There are a few problems related to the existence of several teachers who have not fully understood the learning plan by using the curriculum 2013, which is a tool used by some teachers still using the old model and classroom learning processes that currently focus on the learning process in students (student center) however, there are still many teachers who apply learning using the lecture method only. Based on the results related to the obstacles / obstacles faced by teachers and students in the implementation of the  curriculum 2013 that is 66.67% fully the implementation of the  curriculum 2013 has been implemented and the remaining 33.33% is mostly accomplished this proves that students and teachers do not feel there are obstacles in implementation of the  curriculum 2013